EFFECTIVENESS OF USING SOFTWARE APPLICATIONS TO EVALUATE STUDENTS' KNOWLEDGE AND SKILLS (Scientific journal of the Fergana State University, 2024)
This article aims to develop mechanisms for using modern programs to evaluate young people's knowledge, increase their interest in learning, and determine their rating. Nowadays, accurate knowledge of the reader is one of the most important problems. Therefore, the greatest task assigned to IT representatives is that the development of reliable and effective software is becoming a day-to-day requirement. In recognition of the above ideas, we have identified the following programs for ourselves. These applications are MyTest, Google.Therefore, the greatest task assigned to IT representatives is that the development of reliable and effective software is becoming a day-to-day requirement. In recognition of the above ideas, we have identified the following programs for ourselves. These applications are MyTest, Google Forms, QuizMaker, iSpring Dialog Trainer, and.We may consider all of these apps to be the best and most effective for educating young people in education to acquire their knowledge and skills. For example, through the MyTest app, we can do a number of things, such as productivity, thinking development, and excessive time consumption.The MyTest app is a very convenient and simple-to-use app for evaluating the knowledge of young people, and running it does not require more knowledge and experience from students, and at the same time, any fan teacher can learn this program very quickly and in very little time.